The use of manure and Trichoderma-Beauveria biofertilizer to improve soil chemical properties and crop yield in the rainfed ”surjan” intercropping system - Agustina, Rohmatin; Ariffin, Ariffin; Aini, Nurul; Koestiono, Djoko; Yamika, Wiwin Sumiya Dwi; Khumairoh, Uma (Journal of Degraded and Mining Lands Management, 2026)
The ”surjan” intercropping system, a traditional raised-bed farming practice in which rice is cultivated in furrows and, at the same time, vegetables and legumes are grown on elevated beds, has the potential to sustain food production on rainfed lowlands during the dry season. A factorial randomized block design experiment was conducted to investigate the interaction effects of manure at  0 t ha-1 (M0), 15 t ha-1 (M15), 25 t ha-1 (M25) and a liquid biofertilizer containing Trichoderma spp. and Beauveria bassiana at  0 L ha-1 (L0), 3 L ha-1 (L3),  6 L ha-1 (L6) on soil chemical properties, vegetative growth, and yield of five raised-bed commodities. The treatment interaction significantly improved soil organic carbon (+116.7%) and total nitrogen (+50.0%) relative to initial conditions, while cation exchange capacity declined (-16.3% to -42.6%). Yield responses were commodity-specific: Cucumis sativus L. achieved the highest yield (23.1 t ha-1) at M25×L6 treatment, whereas Vigna unguiculata L. exhibited the greatest proportional responsiveness (+133.3%) at M25×L6 treatment with strong correlations to organic carbon (r = 0.820) and cation exchange capacity  (r = 0.690). Butternut squash responded best at moderate doses (M15×L3 treatment), while Capsicum frutescens L. showed the lowest response to the treatments. The M25×L6 treatment combination yielded the smallest decline in cation exchange capacity (-20.7%) but the greatest accumulation of organic carbon. The optimal amendment formulation is commodity-specific and requires a precision approach for the “surjan” system in rainfed lowlands.